Development of an optical flow through detector for bubbles, crystals and particles in oils. Issue 3 (23rd December 2021) - Birkin, Peter R.; Youngs, Jack J.; Truscott, Tadd T.; Martini, Silvana
Abstract : Oscillating microbubbles, driven by the local sound field, and crystals are detected and sized in oils as they pass through an optical detector. Abstract : The characterisation of bubbles or particles in an oil poses some unique challenges. In contrast to water solutions, the use of electrochemical detection approaches is more difficult in an oil. However, optical sensing systems have considerable potential in this area. Here we use a flow through channel approach and monitor the light propagation through this structure in an optical transmission sensor arrangement (OTS). This simple approach is demonstrated to be useful at detecting bubbles produced in the oil as a result of cavitation induced by high intensity ultrasound (HIU). The optical technique is shown to have an analytical basis. Bubble detection from an operating HIU source is shown to depend on position of the sensor with respect to the source. Critically, the bubble population can be followed for extended time periods after the ultrasonic source has been terminated. The detection of crystals is also demonstrated. Hence, this technique is ideal for the study of the effects of HIU on oils as they crystallise over extended time periods.